2022
DOI: 10.1007/s00167-022-07133-w
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic repair of degenerative medial meniscus tears in patients aged over 45 years resulted in favorable clinical outcomes and low clinical failure rates at a minimum 2-year follow-up

Abstract: PurposeThis study aimed to investigate clinical and radiological results of arthroscopic repair for isolated medial degenerative meniscus tears (DMTs) in patients over 45 years old at a minimum 2‐year follow‐up. MethodsFrom 2013 to 2017, patients aged over 45 years with isolated medial DMT refractory to conservative management or with true mechanical symptoms who had undergone arthroscopic repair were retrospectively reviewed. Arthroscopic meniscus repair was performed using all‐inside or all‐inside and inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Thirteen studies were included in this review, encompassing a total of 316 meniscal repairs in patients over the age of 40 years [10][11][12][13][14][15][16][17][18][19][20][21][22]. There were no randomized controlled studies included or studies where data were collected prospectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies were included in this review, encompassing a total of 316 meniscal repairs in patients over the age of 40 years [10][11][12][13][14][15][16][17][18][19][20][21][22]. There were no randomized controlled studies included or studies where data were collected prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…Where the operative techniques were reported, 63 meniscal repairs used an all-inside technique, 130 used inside-out, and 4 used an outsidein technique. In all-inside meniscus repairs, six studies reported the use of a Fast-Fix© system (Smith & Nephew, Andover, MA, USA) [10][11][12]14,22,23], one study reported the used of Biofix Arrow Fixation© [17], one study reported the use of a VIPER© repair system (Arthrex, Naples, FL, USA) [17], and one study reported the use of a Zone Specific II Meniscal Repair System (Linvatec, Largo, FL, USA) [12]. In studies where meniscus repair was performed using the inside-out technique, a Juggerstitch© Meniscal Repair Device and fast-fix system (Smith & Nephew, Andover, MA, USA) were utilized [10,20].…”
Section: Repair Techniquementioning
confidence: 99%
“…33,37,47,49 This could be explained by the fact that no distinction was made between grade and signal. 33,37,47,49 However, a nuance was brought up in their discussion: the persistence of a grade 3 signal was often associated with the absence of clinical criteria for nonhealing and should be part of the healing process. 33,37,47,49…”
Section: Discussionmentioning
confidence: 99%
“…When the stable leaf receiving additional damage develops an unstable flap, APM will be required [ 9 , 18 ]. Recently, arthroscopic repair was also considered as a reliable option in treating MMHT because the benefit of meniscal repair had been documented [ 23 , 32 ]. However, it is not always possible to confirm the unstable flap on MRI scans [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…If surgeons preoperatively distinguish between those who would benefit from APM and those who would not, unnecessary surgery could be avoided and the outcomes of APM will be improved. Moreover, there is a growing interest in the arthroscopic repair of MMHT [ 23 , 24 ]. Predicting unstable flaps is closely related to surgical indications.…”
Section: Introductionmentioning
confidence: 99%